Strategic noise in competitive markets for the sale of information - Germain, Laurent (Journal of Financial Intermediation, 2005)
This paper shows how informed financial intermediaries can reduce their trading competition by designing optimal incentive compatible contracts for the sale of information. With fund management contracts—indirect sale of information—banks can credibly commit to collaborate and add noise into prices. This is a way to circumvent the Grossman and Stiglitz (1980) paradox: when information is costly, by committing to add noise, the banks can recover the cost of collecting information and enter the market. By contrast, when information is costless, even with a large number of sellers of information entering the market prices are not fully informative.